Mechanisms Underlying Memory Consolidation by Adult-Born Neurons During Sleep - Vergara, Pablo; Sakaguchi, Masanori (Frontiers in Cellular Neuroscience, 2020)
The mammalian hippocampus generates new neurons that incorporate into existing neuronal networks throughout the lifespan, which bestows a unique form of cellular plasticity to the memory system. Recently, we found that hippocampal adult-born neurons (ABNs) that were active during learning reactivate during subsequent rapid eye movement (REM) sleep and provided causal evidence that ABN activity during REM sleep is necessary for memory consolidation. Here, we describe the potential underlying mechanisms by highlighting distinct characteristics of ABNs including decoupled firing from local oscillations and ability to undergo profound synaptic remodeling in response to experience. We further discuss whether ABNs constitute the conventional definition of engram cells by focusing on their active and passive roles in the memory system. This synthesis of evidence helps advance our thinking on the unique mechanisms by which ABNs contribute to memory consolidation.